Можливості дослідження тілопальних поховань: біоархеологічні студії - Слободян, Т.І. (Археологія, 2018)
Статтю присвячено висвітленню основних можливостей та напрямів у дослідженні кісткових решток кремацій. Розглянуто методики фіксації тілопальних поховань в польових умовах з метою отримання більш повної інформації про етапи та особливості поховальних ритуалів. The article is devoted to determination of the main possibilities and directions in the study of ancient cremations. Despite the considerable fragmentation, the analysis of the burnt bones allows us to obtain not only the morphological characteristics of the buried people, sex and age definitions, pathologies, signs of physical development and occupational stress, but also to answer the question about the details of the cremation process, traces of which were almost completely destroyed by the funeral hearth — to establish the maximum temperature of the funeral fire, the position of a body during the process of cremation, the location of the grave goods at the funeral hearth (contact or non-contact), the facts of deliberate actions with the human remains, the selection of cremation remains from the funerary hearth and their insertion in the tomb, the usage of animals in burial ceremonies, etc. Anthropological analysis and the detailed fixation of cremations make it possible to reconstruct more fully and systematically not only the stages and characteristics of the funeral rituals, but also to deduce funeral ceremonial traditions in ancient societies and the status of the deceased members in these societies. Статья посвящена определению основных возможностей и направлений в исследовании костных останков из древних трупосожжений. Несмотря на значительную фрагментарность, анализ кремированных останков позволяет получить не только морфологические характеристики погребенных людей, половозрастные определения, патологии, признаки физического развития, но и ответить на вопрос об обстоятельствах и деталях обряда кремации, следы которого были почти полностью уничтожены огнем — определить температуру погребального кострища, положение тела во время кремации, расположение погребального инвентаря, особенности отбора остатков кремации из погребального костра и последующего их размещения в могиле, использование животных в погребальных обрядах, выделение коллективных захоронений и т.д. Антропологический анализ и подробная фиксация кремаций в полевых условиях позволяют более полно и системно реконструировать не только этапы и особенности погребальных ритуалов, но и общепринятые мировоззренческие и погребальные нормы исторических обществ.